Keanekaragaman dan Kelimpahan Makrozoobentos Sebagai Bioindikator Kualitas Air di Situ Patengan, Kabupaten Bandung, Jawa Barat - Rahmat Taufiq Mustahiq Akbar; Yuni Setiyowati; Ana Widiana; Tri Cahyanto (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Situ Patengan is standing water located at the foot of Mount Patuha, Patengan Village, Rancabali District, Bandung Regency, West Java. Situ Patengan is also used for various activities including as a tourist area, fishing, and tea plantations as well as plantation business rights. The number of activities around Situ Patengan can potentially affect the quality of the waters and the organisms in it, including macrozoobenthos organisms. The presence of macrozoobenthos can also be used as a bioindicator of water quality because it is very sensitive to environmental changes. This study aims to determine the diversity, abundance, and influence of environmental factors on macrozoobenthos and to determine the water quality of Situ Patengan. The research was conducted using the purposive sampling method. Three stations are determined based on environmental factors and land use in the inlet area, forest edge, and tourism area. Based on the results of the study found 3 macrozoobenthos phyla, namely Molluscs (Pomacea canaliculata, Filopaludina javanica), Annelida (Lumbriculus sp.), and Arthropoda (Macrobracium rosenbergii, Enallagma sp., Pelocoris femoratus). Macrozoobenthos diversity ranged from 0.13-1.12 with low to moderate categories while abundance ranged from 11-91 ind/m2 and the Dominance Index in Situ Patengan ranged from 0.003-0.453 with the dominant species being Pomacea canaliculata. The Family Biotic Index shows results from 5.94 to 6.50 with the criteria that the waters at each station are not in good condition. The water quality of Situ Patengan based on macrozoobenthos bioindicators is moderate to heavily polluted. Environmental factors in this study such as depth, brightness, temperature, pH, salinity, and DO have a very low correlation to the family biotic index. Keyword: Bioindicator, diversity, water quality, macrozoobenthos, situ patengan